Urbanização, segundas residências e turismo na zona costeira do Piauí - Pessôa, Fabiana da Silva (2020)
Piauí is the only northeastern state that does not have its Capital located in the coast, has a line of coasts of only 66km long, belonging four piauiense municipalities: Cajueiro da Praia, Ilha Grande do Piauí, Luís Correia and Parnaíba, that together make up the Piauí Coastal Zone. Despite the reduced line of coast, this territory has a prominent part in the economical, historical and social contexts of the state since its occupation and formation, which go back to the second half of the 18thcentury. Nowadays, this holds attractions and services that put it in highlight under various sectors, among them: leisure, tourism— ecological, of business and sun and the sea—commerce, health, education, energy, extractivism, among others, that provides the (re)production of urban spaces and the dynamics in the urbanization process. It is at this juncture that the importance of understanding the urbanization of the piauiense Coastal Zone taking place in the urban spaces, here considered, the urban zone and the coastal spaces of all municipalities in this territory. In front of a previous study, we concluded that, in contemporaneity, there are three urban vectors that stand out in the production and reproduction of the urban spaces of the coastal territory of the state, whatever they may be: socio-spatial aspects, the second residences and tourism. Through this determination, the research problem was established: In the dimension of urbanization and enhancement of coastal spaces, such as the vectors- socio-spatial aspects, the second residences and tourism—acts in the urbanization and production of urban spaces in the Coastal Zone of Piauí? To elicit the answers to this questions, the objective was to analyze the urban vectors – socio-spatial aspects, the second residences and tourism – in the urbanization configuration, valorization and (re)production of urban spaces in the Coastal Zone of Piauí. For the analysis of the vectors established here, distinct but adequate methodologies were used for each vector. The “socio-spatial aspects in the Coastal Zone of Piauí” was analyzed from data related to the time frame from 1990 to 2018 of the urban spaces of the municipalities that composes the CZ piauiense, that were organized in five categories: population, economic, social, structural/local and institutional factors. The vector “second residences” was analyzed through IBGE data about occasional households, as well as through field research and application of questionnaires to the owners and / or occupants of these households. The “tourism” vector was analyzed through a field research that identified the kinds and forms of occupation of the Coastal Zone, focused on tourism, as well as application of questionnaires to owners and/or employees of the accommodation facilities. Regarding the structure, this thesis was organized in four chapters, besides introduction and conclusion: i) The Piauiense Coastal Zone; ii) Territorial formation and urbanization in the Coastal Zone of Piauí; iii) Socio-spatial aspects of the Piaui Coastal Zone; iv) The Second residences and tourismo: modern maritime practices in the urbanization of the Piaui Coastal Zone.